THE DEVELOPMENT OF COOPERATION AMONG THE SHANGHAI COOPERATION ORGANIZATION (SCO) MEMBER STATES IN THE FIELD OF TOURISM - Nigmatov Alisher Khayrullayevich (Bright Mind Publishing, 2026)
This article examines the development of cooperation in the field of tourism among the Member States of the Shanghai Cooperation Organization (SCO), highlighting tourism as one of the most promising and rapidly evolving areas of multilateral partnership within the organization. In recent years, SCO countries have undertaken various joint initiatives aimed at strengthening cultural exchange, improving tourism infrastructure, simplifying visa procedures, and promoting combined tourist routes across the region. The article provides analytical insights into these initiatives, evaluates their effectiveness, and identifies the main factors contributing to the growth of intra-regional tourism. Furthermore, it explores the role of governmental and intergovernmental programs, specialized forums, and cooperation platforms that facilitate dialogue and coordination among national tourism administrations. By reviewing statistical trends and practical steps taken by SCO members, the study demonstrates that tourism cooperation is becoming an important component of regional integration, economic development, and mutual understanding among the peoples of SCO countries. Overall, the article shows that tourism within the SCO framework is developing steadily, creating new opportunities for sustainable growth and long-term partnership.
Keywords: SCO, Tourism, Economy, Development, UNWTO, Tashkent, Cooperation